Effectiveness of Norepinephrine-Vasopressin Combination in Reducing Mortality in Septic Shock Patients: A Scoping Review - Ratih Puspita Febrinasari; Kenneth Tan; Astrida Fesky Febrianty; Yusuf Ari Mashuri (Universitas Sebelas Maret, 2022)
Sepsis and septic shock are the major health problems worldwide, including in Indonesia. Sepsis and septic shock are medical emergencies that require adequate prompt resuscitation to reverse tissue hypo-perfusion, which will prevent patient mortality. The latest international guideline on septic shock treatment recommended norepinephrine as a first-line vasopressor followed by dopamine and dobutamine as an alternative vasopressor. However, the practices still vary. Therefore, a scoping review is required to scope the existing article, summarize scientific evidence, and give a bearing on future research regarding the effectiveness of norepinephrine-vasopressin combination in reducing mortality in septic shock patients. This scoping review was covered articles published after 2011. A total of 953 articles were collected. Seven articles comprised of 5 systematic reviews, 1 randomized controlled trial, and 1 cohort study with a total 21,670 of patients, were included for qualitative synthesis. From the analysis, there had not been enough scientific evidence to conclusively determine the combination of vasopressors as the best therapeutic outcome of sepsis treatment. In conclusion, based on the existing articles there is inadequate scientific evidence to definitively conclude the effectiveness of the combination of vasopressors and norepinephrine for the treatment of septic shock patients. Further research is needed to explore the effectiveness of the norepinephrine-vasopressin combination in reducing mortality in septic shock patients.